2000
DOI: 10.1046/j.1365-2818.2000.00724.x
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray microanalysis of cultured keratinocytes: methodological aspects and effects of the irritant sodium lauryl sulphate on elemental composition

Abstract: Irritant substances have been shown to induce elemental changes in human and animal epidermal cells in situ. However, skin biopsies are a complicated experimental system and artefacts can be introduced by the anaesthesia necessary to take the biopsy. We therefore attempted to set up an experimental system for X‐ray microanalysis (XRMA) consisting of cultured human keratinocytes. A number of methodological aspects were studied: different cell types, washing methods and different culture periods for the keratino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…3 Increased levels of magnesium and calcium ions, which may play a role in cell proliferation and differentiation, have been described in psoriatic keratinocytes and after sodium laurylsulfate-induced irritation. 4,5 Early in the process of wound healing the concentration of magnesium ions in wound fluid from porcine and rat skin is elevated. [6][7][8] Hairless rats fed a low magnesium diet developed a raised patchy erythematous rash consisting of nonfollicular plaques and papules.…”
Section: Introductionmentioning
confidence: 99%
“…3 Increased levels of magnesium and calcium ions, which may play a role in cell proliferation and differentiation, have been described in psoriatic keratinocytes and after sodium laurylsulfate-induced irritation. 4,5 Early in the process of wound healing the concentration of magnesium ions in wound fluid from porcine and rat skin is elevated. [6][7][8] Hairless rats fed a low magnesium diet developed a raised patchy erythematous rash consisting of nonfollicular plaques and papules.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of this are post-mortem changes in elemental content (Kuijpers and Roomans, 1980), various types of injury such as chemical, mechanical or radiation injury (e.g., Grängsjö et al, 1996;Wróblewski et al, , 2002, or changes due to anoxia, such as happens when tissue is removed from an experimental animal (Hongpaisan et al, 1996). Exposure of cultured cells to toxic or noxious substances will result in a similar pattern of elemental changes (Kampf et al, 1999;Grängsjö et al, 2000a;Kampf and Roomans, 2001). Also transient cell damage will give rise to changes with this pattern, although it is well possible that the changes are reversed when the cells recover (Hongpaisan et al, 1996).…”
Section: Elemental Changes Associated With Cellular Processesmentioning
confidence: 99%
“…The cellular concentration of P mainly reflects the phosphate groups of the nucleic acids (DNA and RNA). The preferred cations for these phosphate groups are K + and Mg 2+ , so it is to be expected that these elements follow the changes in P. Co-variance in Mg, P and K concentrations is frequently observed (Grängsjö et al, 2000a). If elemental ratios are used instead of absolute concentrations, the K/Na ratio (or the Na/K ratio) is a sensitive indicator.…”
Section: Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies have shown that magnesium bromide and magnesium chloride inhibits the well‐known excessive proliferation of psoriatic keratinocytes 3 . Increased levels of magnesium and calcium ions, which may play a role in cell proliferation and differentiation, have been described in psoriatic keratinocytes and after sodium laurylsulfate‐induced irritation 4,5 . Early in the process of wound healing the concentration of magnesium ions in wound fluid from porcine and rat skin is elevated 6–8 .…”
Section: Introductionmentioning
confidence: 99%